The effect of the thermoplastic nilon enterprises (valplast) on clove extract (syzygium aromaticum) in various concentrations on the color change - Niken Wibawaningtyas; Dewi Kristiana; Niken Probosari (DiscoverSys Inc., 2017)
Objective: To investigate the effect of soaking of thermoplastic nylon (valplast) on clove flower extract (syzygium aromaticum) as a denture cleanser with different concentration 0.8%, 1%, 1.2%, 1.4%, and 1.6% to the color change of thermoplastic nylon.Material and Methods: 30 samples were divided into 6 groups. The sample size is (10x10x1) mm. The first group was immersed in sterile aquades and the other groups were immersed in clove flower extracts of 0.8%, 1%, 1.2%, 1.4%, and 1.6% for 12 days. The light intensity then measured using densitometer.Results: One way anova test results obtained value 0.174 (p>0.05) which indicates that there is no significant difference in each group.Conclusions: This study are darker discoloration of the thermoplastic nylon at a concentration of 1.6% and lower color changes occurring at a concentration of 0.8%.